Electrodeposition of Copper Composites (Alumina Nano and Micro Particle Size) from Ionic Liquid (Ethaline) using Acoustic Impedance Electrochemical Quartz Crystal Microbalance (EQCM) at Cut Working Electrode in “Vertical” Position (London Journal of Engineering Research, 2024)
Here we trace the electrolytic deposition of copper and copper composites from a solution of the metal chloride salt in ethylene glycol / choline chloride based eutectics. This work also explores the use of the electrochemical quartz crystal microbalance (EQCM) to monitor both the deposition and the inclusion of inert particulates into the copper coatings. This technique allows the first in-situ the determination the thickness of coated copper beside particulate inclusion. However the composition of composite material was strongly dependant on the amount of species suspended in solution and the size of incorporated alumina particles. It was also revealed that the majority of material was dragged onto the surface that has been shown in the difference on thickness between copper coated with 50 nm and 1? alumina.
Keywords: Particleboard; urea-formaldehyde resin; curing agents; modifier-curing agent; copper composites; ionic liquid; alumina; EQCM and SEM